Biological activities and genome of marine Streptomyces verrucosisporus CPB1-1T - Wongsakorn Phongsopitanun; Pawina Kanchanasin; Paranee Sripreechasak; Pattama Pittayakhajonwut; Somboon Tanasupawat (Agriculture and Natural Resources, 2021)
The CPB1-1T strain of Streptomyces verrucosisporus has been isolated from marine sediment in Thailand. The objective of this study was to determine for the first time the biological activity and to obtain the genome sequence of this type strain. The crude ethyl acetate extract of the type strain had potent antibacterial activity against Gram-positive bacteria (Bacillus cereus and Enterococcus faecium) with a minimum inhibitory concentration (MIC) of 1.56 μg/mL. In addition, it showed anti-Mycobacterium tuberculosis activity with a MIC value of 6.25 μg/mL. The crude extract had no activity against the Gram-negative bacteria Plasmodium falciparum, nor cancer cell lines. The genome analysis revealed that the strain CPB1-1T had several biosynthetic gene clusters of secondary metabolites including terpene, polyketide, lanthipeptide, lasso peptide and thiopeptide.